1993
DOI: 10.1016/0165-2427(93)90100-i
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bovine immunodeficiency-like virus infection on immune function in experimentally infected cattle

Abstract: Bovine immunodeficiency-like virus (BIV) is a bovine lentivirus that has antigenic and genetic homology with the human immunodeficiency virus. Little work has been reported on the effect of BIV infection on bovine immune function. This study was designed to evaluate lymphocyte blastogenesis, mononuclear cell subset numbers, neutrophil function, hematology, and clinical signs in three groups of cattle. These groups were evaluated at 0-2 months post inoculation (PI, Group 1), 4-5 months PI (Group 2), or 19-27 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 26 publications
1
46
1
Order By: Relevance
“…Proviral DNA of BIV was also detected in bull semen [17], and the seroprevalence of BIV infection increases according to aging of animals in the same dairy herd, suggesting that BIV would be possibly transmitted through natural or artificial inseminations, and/or through blood instrument or blood sucking insects [22]. Moreover, pathogenesis of this virus still remains unclear although BIV infections can induce dysfunction of monocytes [18], neutrophils [6] and BIV proviral DNA was also detected in various organs from the cow naturally infected with BIV by nested-PCR systems targeting the pol region [13]. In conclusion, this study can provide additional information about contribution of BIV infection in various countries around the world.…”
mentioning
confidence: 99%
“…Proviral DNA of BIV was also detected in bull semen [17], and the seroprevalence of BIV infection increases according to aging of animals in the same dairy herd, suggesting that BIV would be possibly transmitted through natural or artificial inseminations, and/or through blood instrument or blood sucking insects [22]. Moreover, pathogenesis of this virus still remains unclear although BIV infections can induce dysfunction of monocytes [18], neutrophils [6] and BIV proviral DNA was also detected in various organs from the cow naturally infected with BIV by nested-PCR systems targeting the pol region [13]. In conclusion, this study can provide additional information about contribution of BIV infection in various countries around the world.…”
mentioning
confidence: 99%
“…A Canadian group (Archamboult et al, 1993) confirmed the p26 occurrence in cattle, sheep, goats and rabbits, but they could not prove any BIV-induced immune response disturbance as follows infections with HIV. Flaming et al (1993) reported that BIV infections were associated with an increase in the lymphoblastic response to the mitogen phytohemagglutinin and a decrease in the neutrophil antibody-dependent cell-mediated cytotoxicity and neutrophil iodination but nothing else and in 1995, Rovid et al concluded that antibody-dependent cell-mediated cytotoxicity was not observed. In the same year, Nash et al (1995) suggested that BIV might be transmitted via semen.…”
Section: Experimental Inoculations and Natural Infectionsmentioning
confidence: 99%
“…Similarly, transfer of bovine immunodeficiency virus, which is innocuous in Bos taurus, to Bos javanicus resulted in a severe epidemic of lethal Jembrana disease (11,36). Even in cases where lentiviruses cause disease, many infected individuals remain infected but symptom free over their natural lifetime, with a continual production of infectious virus despite a vigorous immune response.…”
mentioning
confidence: 99%